Information and Knowledge Seeking Behaviors: A Scientific Review (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to provide an analytical review of 15 studies on knowledge seeking behaviors. This study aims; to explore information and knowledge seeking behaviors, analyze the different perspectives on this topic, understand the main trends in information and knowledge seeking that were focused on, and identify the main findings and conclusions reached by these studies. The importance of this study lies in the need for a deeper understanding of information and knowledge seeking behaviors. This study was conducted based on the descriptive analytical approach and the use of content analysis as a tool. It reached several conclusions that weak research skills are a major challenge affecting the quality of scientific research, which calls for curriculum development and training workshops to improve these skills. Social, psychological and economic factors also play a role in hindering the search for knowledge, while the shift towards the digital environment has allowed for faster access to information, but it also revealed the need to train researchers to use digital tools effectively. Digital libraries need continuous improvement to meet the needs of users. Academic curricula should focus on linking theoretical knowledge to practical applications. The study recommended studies on the relationship between group dynamics and individual research behaviors, as well as analyzing and comparing research behaviors between different communities. As well as analyzing the impact of digital research systems on researchers' interaction with knowledge compared to traditional systems, designing new evaluation metrics to measure the effectiveness and quality of research behaviors. And analyzing how research behavior integrates with knowledge-sharing behavior to enhance the research environment.
Keywords: Information-seeking behavior; knowledge-seeking behavior; research behaviors; research skills; research strategies